RESPON PERTUMBUHAN PADI GOGO LOKAL YANG DIBERI BAHAN ORGANIK PADA BERBAGAI KONDISI KETERSEDIAAN AIR - Sari, Nina Yunita; Ete, Andi; Made, Usman (AGROTEKBIS, 2017)
Research aimswas to studies the of response localrainfed lowland riceon the application of organic matter invarious condition of thewater availability. Research was carried out in February until June 2015, in a screen house of BalaiBenih, Petobo Sub-district, South Palu, Central Sulawesi.This study was arranged infactorial randomized block design,first factor was the availability of water, consists of 4 levels that were the field capacity, 85% of the field capacity, 70% of the field capacity, and55 % of field capacity.The second factor consisting of two rates of organic matter, namely without bokashi fertilizer andbokashi fertilizer.Every treatment was repeated three times so there are 24 units of experiments.Every unit of experiment consisting of 2 plants so there are 48 populations of plant. The result showed that the application of 70% of field capacity can obtain higher plant andmore younger plant than others treatment at the beginning growth. The application of organic matter seem no effect at the beginning growth. There is no significant difference of the application of organic matter at all the availability of water condition. Keywords : Gogo local rice , Organic material, and The availability of water.